The motorcycle diaries : notes on a Latin American journey - Guevara, Ernesto, 1928-1967.; Keeble, Alexandra (Melbourne, Australia ; New York : Ocean Press, 2004)
A chronicle of the author's seven-month motorcycle journey throughout South America reveals the beginning of his transformation into a dedicated revolutionary. Special movie tie-in edition of Che Guevara's youthful travel diaries to coincide with the Fall release of Redford & Salles's film of the book. Says director Walter Salles: "If the film reaches a younger audience, I hope it will inspire people to read The Motorcycle Diaries, to have the impression that change can occur." "As his journey progresses, Guevara's voice seem to deepen, to darken, colored by what he witnesses in his travels. He is still poetic, but now he comments on what he sees, though still poetically, with a new awareness of the social and political ramifications of what's going on around him."-January Magazine "The Motorcycle Diaries could easily go on to become the first Spanish language nominee for Best Picture."-Roger Friedman, Fox News.
So we understand each other -- Forewarnings -- Discovery of the ocean -- ...Lovesick pause -- Until the last tie is broken -- For the flu, bed -- San Martín de los Andes -- Circular exploration -- Dear Mama -- On the Seven Lakes Road -- And now, I feel my great roots unearth, free and... -- Objects of curiosity -- The experts -- The difficulties intensify -- La Poderosa II's final tour -- Firefighters, workers and other matters -- La Gioconda's smile -- Stowaways -- This time, disaster -- Chuquicamata -- Arid land for miles and miles -- The end of Chile -- Chile, a vision from afar -- Tarata, the new world -- In the dominions of Pachamama -- Lake of the sun -- Toward the navel of the world -- The navel -- The land of the Incas -- Our Lord of the Earthquakes -- Homeland for the victor -- Cuzco straight -- Huambo -- Ever northward -- Through the center of Peru -- Shattered hopes -- The city of the viceroys -- Down the Ucayali -- Dear Papi -- The San Pablo leper colony -- Saint Guevara's day -- Debut for the little Kontiki -- Dear Mama -- On the road to Caracas -- This strange 20th century -- A note in the margin -- Appendix. A child of my environment (Speech to medical students, 1960).
Includes bibliographical references.
Translation of: Notas de viaje.
edited hb 2015-06-16
Keywords: Guevara, Ernesto, -- 1928-1967 -- Diaries; Guevara, Ernesto, -- 1928-1967 -- Travel -- Latin America; Latin America -- Description and travel